An evaluation of possible interactions between ethanol and trazodone or amitriptyline. - Warrington, S J (1984)
The pharmacodynamic effects of single doses of trazodone (100 mg), amitriptyline (50 mg) or placebo either alone or with ethanol (0.5 ml/kg) were investigated in six healthy volunteers in a double-blind crossover study. Plasma concentrations of the drugs and ethanol were also measured. Pharmacodynamic tests were critical flicker fusion frequency threshold (CFF), choice reaction time (CRT), manual dexterity, a digit span test and visual analogue scales. Blood ethanol concentrations were not influenced by the co-administration of either antidepressant. tmax for trazodone was prolonged by ethanol but the other pharmacokinetic parameters for trazodone and amitriptyline were not influenced by ethanol. Trazodone and amitriptyline caused the expected profound depressant effects on CFF, CRT, manual dexterity and on the rating scales for drowsiness, 'clear-headedness', aggression and disinhibition. Ethanol alone impaired manual dexterity, increased drowsiness, reduced 'clear headedness' and also tended to reduce feelings of aggression. In combination with either trazodone or amitriptyline, ethanol caused little additional effect except in the case of manual dexterity which was further impaired. This result may reflect the profound effects of the antidepressants alone and does not suggest that it is safe for patients receiving antidepressant medication to take ethanolic drinks.